Pericardial cyst causing cardiac compression and shunt reversal at atrial level - Acharya, Anil; Koirala, Raamesh; Rajbhandari, Nivesh; Panthee, Nirmal (Nepalese Heart Journal, 2018)
Pericardial cyst is a rare disorder with incidence of 1:100000 and is usually asymptomatic. Atrial septal defect on the other hand has incidence of 1.6:1000 live births with 97% chance of survival till adulthood and rarely causes Eisenmenger syndrome in early adulthood. We present a case where there was dramatic occurrence of sudden hypoxia and features of right heart failure in otherwise healthy adult because of the combination of these two entities.